MoneyMingle: bridging financial literacy and experience through interactive loan education app / Muhammad Irsyad Hilmi Ahmad Azman … [et al.] - Ahmad Azman, Muhammad Irsyad Hilmi; Hafizan Raai, Nur Natasha; Abdul Musarwair, Ahmad Farhan Firas; Zaharin, Nur Antasha 'Aeishah; Muhammad Ridhwan, Nur Aziera Nabilla Binti; Omar, Rabiatul Adawiyah Nurul Ain; Mahmud, Nurazree (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In the ever-evolving world of finance, the "MoneyMingle" app presents itself as a creative way to introduce youngsters to credit scores and loans at an early age. By allowing users to mimic loan processes, the app addresses the issue of adolescent financial illiteracy and promotes a better knowledge of financial responsibility. Employed people may also obtain modest loans through a special feature, and students can participate in practical learning. The two goals of the app are to give students actual experience for loan applicants and to equip them with fundamental financial skills. Its uniqueness resides in how it combines practical application with academic information to provide a hands-on approach to financial education. User-friendly interfaces and specially designed learning modules emphasize practicality while guaranteeing accessibility for users from all backgrounds. By bridging the gap between academic knowledge and real-world experience, "MoneyMingle" marks a revolutionary change in financial education and produces a generation of financially knowledgeable individuals who are ready for success. Students may use modest loans for necessities like computers, and working people can use larger loans for major purchases like vehicles, so they can better comprehend a range of financial situations.